Evaluation of Analgesic, Antioxidant, Cytotoxic and Thrombolytic Potential of Stachytarpheta cayennensis (Rich.) Vahl Leaves - Jaman, Asif Uj; Akhter, Sharmin; Shahriar, Saimon; Hawlader, Md Bappy; Islam, Mehedi; Rashid, Mohammad A (Bangladesh Pharmaceutical Journal, 2023)
The current study was undertaken for the preliminary investigation of the analgesic, cytotoxic, antioxidant, and thrombolytic properties of the methanolic extract of Stachytarpheta cayennensis (Rich.) Vahl leaves. Both the central and peripheral analgesic action of the crude extract of methanol were significant and the analgesic effect increases with the increasing of dose and time with the pronounced effect at 600 mg/kg body weight. According to the brine shrimp lethality bioassay, the pet-ether soluble fraction (PESF) displayed notable cytotoxic action showing LC50 value (5.33 μg/ml) among the fractions as compared to the standard vincristine sulfate (0.452 μg/ml) and crude extract of the leaves contained a total phenolic content ranging from 18.68-145.98 mg of GAE/gm while revealing moderate thrombolytic activity. Bangladesh Pharmaceutical Journal 26(1): 45-50, 2023 (January)